Experts and beginners benefit from three-dimensional echocardiography: a multicenter study on the assessment of mitral valve prolapse - Hien, Maximilian; Großgasteiger, Manuel; Rauch, Helmut; Weymann, Alexander; Bekeredjian, Raffi; Rosendal, Christian (Journal of the American Society of Echocardiography, 2013)
Background - Three-dimensional (3D) transesophageal echocardiography (TEE) has been claimed to provide more information than two-dimensional (2D) TEE in the localization of mitral valve prolapse (MVP). However, most studies have been performed by experts in echocardiography, without accounting for differences in training or expertise. This multicenter study was designed to assess the differences between experts and inexperienced echocardiographers in localizing MVP and ruptured chordae tendineae using 2D and real-time 3D TEE. - Methods - Thirty-six observers from 10 institutions in Germany and Switzerland interpreted 2D and 3D transesophageal echocardiographic images from six patients selected to represent a large spectrum of MVP diversity. Surgical findings served as a reference. Individual performance in the prediction of pathology was scored. Differences between 15 experts and 21 beginners in TEE were assessed, and the benefits conferred by 3D TEE were compared. - Results - Both study groups scored significantly higher when interpreting 3D transesophageal echocardiographic images (P ≤ .001). The experts were superior in 2D MVP localization (14.8%; P ≤ .001), a difference that diminished with 3D TEE (1.4%; P = .41). The benefit of access to 3D information for MVP localization was greater for inexperienced echocardiographers compared with experts (P < .001). - Conclusions - The reported diagnostic advantage of 3D TEE over 2D TEE in MVP assessment for expert echocardiographers can be transferred to inexperienced echocardiographers. Inexperienced echocardiographers benefit from the technology to a greater extent than their expert colleagues.